Range-reference determination of lymphocyte subsets in Moroccan blood donors - Touil, N (Makerere Medical School, 2012)
BACKGROUND: Information on lymphocyte populations (T, B, and Natural killer cells) and subpopulations (CD4 and CD8) in Morocco is scarce if not inexistent. OBJECTIVE: To establish a reference value of these cells in 242 Moroccan young adult blood donors by flow cytometry. RESULTS: Smokers had significantly higher total leukocyte count (p < 0.001), total lymphocyte count (p < 0.0001) and higher CD3+CD4+ cells (p < 0.0001). The percentage of CD3-CD56+ subsets was affected by smoking (p < 0.01). Our analysis positively correlate with previous observations of an increase of absolute CD4+ T cells, with no changes in other lymphocyte subset cells in smokers. The lymphocyte subpopulation distributions for all antigens were found to be similar to those reported in Saudi and Italian adults, while higher levels were reported for the same gender in other countries, especially Ghana and Kuwait. CONCLUSION: The international classification standards of the HIV-infected subjects according to their rates of CD4 are applicable to the present study's population.